Prediction of an inverse heavy-atom effect in H-C-CH(2)Br: bromine substituent as a pi acceptor - Havlas, Zdenek; Michl, Josef (Journal of the American Chemical Society, 2002)
A comparison of spin-orbit coupling calculated [CASSCF(6,6)/(cc-pVDZ on C,H and VDZ+P on Br] for bromomethylcarbene and methylcarbene predicts a highly unusual inverse heavy-atom effect by the Br substituent, particularly at geometries near the syn conformation. This behavior is due to a vacant 4d orbital on the Br atom acting as a weak pi-electron acceptor and overwhelming the even weaker effect of the pi-symmetry lone pair donor 4p orbital, which in itself would cause a small normal heavy-atom effect.